2021
DOI: 10.2478/aucft-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fermentation Conditions for Cell Envelope Proteinase Produced by Lactobacillus Plantarum LP69

Abstract: Cell-envelope proteinases (CEPs) can hydrolyze casein into functional peptides, which is beneficial to the health of the host. The single factor experiment screened out that the optimal conditions for CEP production by Lactobacillus plantarum LP69 were 37°C, 20h, initial pH of 7, and optimal inoculation amount of 5%. The best conditions for this experiment were obtained by orthogonal experiment: time 22h, temperature 39°C, initial pH value of 6, and inoculation amount of 5%. Under this culture condition, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Ren (2014) conducted orthogonal experiments on the carbon source and nitrogen source of the cell-envelope proteinase produced by Lactobacillus acidophilus JQ-1, and found that the best combination of carbon source and nitrogen source was 2% glucose + 1% beef peptone. In the previous work, our laboratory screened out that Na2HPO4, inulin, casein peptone and leucine had a significant effect on the CEP production by Lactobacillus plantarum LP69 through the Plackett-Burman experiment (Cheng et al, 2019a;Cheng et al, 2019b;Cheng et al, 2019 c) and optimized the fermentation condition (Zhang et al, 2021). On this basis, this experiment further screened the optimal medium formula for CEP production by Lactobacillus plantarum LP69 through Box-Behnken design and response surface optimization, and provided some references for subsequent industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Ren (2014) conducted orthogonal experiments on the carbon source and nitrogen source of the cell-envelope proteinase produced by Lactobacillus acidophilus JQ-1, and found that the best combination of carbon source and nitrogen source was 2% glucose + 1% beef peptone. In the previous work, our laboratory screened out that Na2HPO4, inulin, casein peptone and leucine had a significant effect on the CEP production by Lactobacillus plantarum LP69 through the Plackett-Burman experiment (Cheng et al, 2019a;Cheng et al, 2019b;Cheng et al, 2019 c) and optimized the fermentation condition (Zhang et al, 2021). On this basis, this experiment further screened the optimal medium formula for CEP production by Lactobacillus plantarum LP69 through Box-Behnken design and response surface optimization, and provided some references for subsequent industrial applications.…”
Section: Introductionmentioning
confidence: 99%